Mechanical Lateral Distal Femoral Angle (MLDFA), Medial Proximal Tibia Angle (MPTA), and Mechanical Axis Deviation (MAD) Value in Young Adults in North Sumatera - Iman Dwi Winanto; Yoyos Dias Ismiarto (PT. Kalbe Farma Tbk., 2022)
Introduction. Reference value to determine the angle of lower extremity is only based on clinical measurement and radiological assessment, which is limited to tibiofemoral angle (TFA). Although this examination can estimate the lower extremity angle, it is not satisfactory for a comprehensive analysis. Material and Method. A descriptive study in RSUP Haji Adam Malik Hospital in August - September 2019 to measure mechanical lateral distal femoral angle (MLDFA), medial proximal tibia angle (MPTA), and mechanical axis deviation (MAD). Results. Thirty nine subjects were included in this study. The mean age was 26.77±4,65 years old (range: 22 to 39 years); 69,2% were male (n = 27) and 30,8% were female (n = 12). The average mechanical lateral distal femoral angle (MLDFA) was 87,93o ±2,16o . The average medial proximal tibia angle (MPTA) was 86,28o ±2,26o . The average mechanical axis deviation (MAD) was 1.56±1,48 mm. Our results of MLDFA and MPTA measurement, but not in MAD, are consistent with study conducted by Farr, et al. Conclusion. Our MLDFA, MPTA, but not MAD measurement results are similar to studies involving Caucasian population.Pendahuluan. Nilai acuan sudut pada ekstremitas bawah hanya berdasarkan pemeriksaan klinis dan radiologis, yang terbatas pada sudut tibiofemoral. Pemeriksaan sudut tibiofemoral (STF) tunggal tidak cukup untuk analisis komprehensif ekstremitas bawah. Bahan dan Cara. Penelitian deskriptif di RSUP Haji Adam Malik pada bulan Agustus – September 2019 untuk mengukur sudut mekanik lateral distal femur (SMLDF), sudut medial proksimal tibia (SMPT), dan deviasi aksis mekanik (DAM). Hasil. Sejumlah 39 subjek diteliti. Usia rata-rata 26,77 ± 4,65 tahun (22 - 39 tahun); 69,2% pria (n = 27) dan 30,8% wanita (n = 12). Nilai rata-rata sudut mekanik lateral distal femur (SMLDF) adalah 87,93º ± 2,16º. Nilai rata-rata sudut medial proksimal tibia (SMPT) adalah 86,28º ± 2,26º. Nilai rata–rata deviasi aksis mekanik (DAM) adalah 1.56 ± 1,48 mm. Pada penelitian ini, hasil pengukuran SMLDF dan SMPT sesuai hasil penelitian Farr, et al, tetapi hasil pengukuran DAM tidak sesuai. Simpulan. Nilai SMLDF dan SMPT pada penelitian ini tidak berbeda dengan penelitian pada populasi Kaukasia